The efficacy of acupuncture for diabetic peripheral neuropathy: a systematic review and meta-analysis of randomized controlled trails - Ge, Ruisi; Liu, Rihe; He, Mengru; Wu, Jiawei; Zhang, Feng; Huang, Chang (Frontiers in Neurology, 2024)
ObjectiveTo systematically evaluate the clinical efficacy of acupuncture in the treatment of diabetic peripheral neuropathy (DPN).MethodsRandomized controlled trial (RCT) of acupuncture for diabetic peripheral neuropathy in Chinese Knowledge Network (CNKI), Wanfang database, VIP database (VIP), PubMed, web of science, cochrane library, AMED and CINAHL were searched by computer since the establishment of the database. All publications in English and Chinese as of 30 December 2023 will be searched, without country or article type restrictions. Study selection, data extraction and evaluation were performed independently by two researchers. Risk of bias was assessed using the Cochrane risk assessment tool, and Meta-analysis was performed using RevMan5.3 software.ResultsDPN has good effective rate in acupuncture than conventional western medicine alone. However, the above conclusions need to be verified by larger samples and higher quality randomized controlled trials. ① Acupuncture treated DPN more effective than drug (RR = 1.38, 95%CI = 1.26 1.51, Z = 6.93, p < 0.00001), DPN of patients with acupuncture plus drug (RR = 1.38, 95%CI = 1.05 1.82, Z = 2.28, p = 0.02), There was no significant difference between acupuncture and usual care (RR = 2.41, 95%CI = 0.70 8.29, Z = 1.39, p = 0.16); ② Acupuncture treatment is superior to drug group in improving the SNCV of the median nerve (MD = 1.65, 95%CI = 0.74 2.57,Z = 3.55, p = 0.0004), sham needle treatment (MD = 0.50, 95%CI = 0.17 0.83, Z = 2.95, p = 0.003), Acupuncture plus drug was superior to drug in improving the SNCV of the median nerve (MD = 3.29, 95%CI = 2.55 4.03, Z = 8.70, p < 0.00001); ③ Acupuncture treatment is superior to drug group in improving the MNCV of the median nerve (MD = 2.24, 95%CI = 0.50 3.98, Z = 2.52, p = 0.01), and sham needle treatment (MD = 0.20, 95%CI = −0.03 0.43, Z = 1.69, p = 0.09), Acupuncture plus drug was superior to drug group in improving the MNCV of the median nerve (MD = 2.63, 95%CI = 1.83 3.42, Z = 6.46, p < 0.00001); ④ Acupuncture is better to drug group in improving SNCV of common peroneal nerve (MD = 1.67, 95%CI = 0.21 3.13, Z = 2.24, p = 0.02); ⑤ Acupuncture treatment is superior to drug group in improving the MNCV of the common peroneal nerve (MD = 2.03, 95%CI = 1.37 0.69, Z = 6.04, p < 0.00001), Acupuncture plus drug outperformed MNCV in improving the common peroneal nerve (MD = 4.23, 95%CI = −0.16 8.62, Z = 1, 89, p = 0.06); ⑥ Acupuncture treatment is superior to drug group in improving the SNCV of the tibial nerve (MD = 1.58, 95%CI = 0.85 2.30, Z = 4.26, p < 0.0001); ⑦ There was no significant difference between acupuncture treatment and drug group in improving the MNCV of the tibial nerve (MD =1.55, 95%CI = −0.59 3.68, Z = 1.42, p = 0.16); ⑧ Acupuncture plus drug is better than medication in reducing VAS (MD = −2.35, 95%CI = -3.78 −0.93, Z = 3.23, p = 0.001), Acupuncture plus usual care is superior to usual caret (MD = −28.70, 95%CI = -39.50 17.90, Z = 5.21, p < 0.00001), There was no significant difference between acupuncture and sham needle treatment (MD = −4.00, 95%CI = -18.32 10.32, Z = 0.55, p = 0.58).ConclusionCompared with drug, usual care, and sham AT, AT has a better response rate and more favorable effect in improving nerve conduction velocity. The combination of AT and drug demonstrates a more significant improvement compared to drug alone. The combination of AT and usual care improves DPN symptoms more effectively than usual care. However, the above conclusions need to be verified by larger samples and higher quality randomized controlled trials.Systematic review registration[https://www.crd.york.ac.uk/], identifier [CRD42023451575].